Effect of Exercise-Related Factors on the Perception of Time - Behm, David G.; Carter, Tori B. (Frontiers in Physiology, 2020)
The concept of time whether considered through the lenses of physics or physiology is a relative measure. Alterations in time perception can have serious implications in sport, fitness and work. Accurate perception of time is an important skill with many time constrained sports (i.e. basketball, North American football, tennis, gymnastics, figure skating, ice hockey and others), and work environments (i.e. workers who need to synchronize their actions such as police and military). In addition, time distortions may play a role in exercise adherence. Individuals may be disinclined to continue with healthy, exercise activities that seem protracted (time dilation). Two predominant theories (scalar expectancy theory and striatal beat frequency model) emphasize the perception of the number of events in a period and the role of neurotransmitters in activating and coordinating cortical structures respectively. A number of factors including age, sex, body temperature, state of health and fitness, mental concentration and exercise intensity level have been examined for their effect on time perception. However, with the importance of time perception for work, sport and exercise, there is limited research on this area. Since work, sports, and exercise can involve an integration of many of these aforementioned factors, they are interventions that need further investigations. The multiplicity of variables involved with work, sport, and exercise offer an underdeveloped but fruitful field for future research. Thus, the objective of this review was to examine physiological and psychological factors affecting human perception of time and the mechanisms underlying time perception and distortion with activity.